2013
DOI: 10.1021/ol4016404
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside 3′,5′-Cyclic H-Phosphonates, New Useful Precursors for the Synthesis of Nucleoside 3′,5′-Cyclic Phosphates and Their Analogues

Abstract: Nucleoside H-phosphonates activated with a condensing agent spontaneously formed nucleoside 3',5'-cyclic H-phosphonates. The cyclization was stereoselective and produced one of the P-diastereomers in preponderance (de ca. 80%). Nucleoside 3',5'-cyclic H-phosphonates were stereochemically unstable and underwent epimerization affording the thermodynamically more stable diastereomer as a major product (de ca. 80%). They were susceptible to hydrolysis, transesterification, and oxidation and by changing oxidation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Accordingly, an alternative method is needed for the efficient protection of 3Ј,5Јcyclic phosphodiesters with enzymatically removable groups. We now show that the oxidative coupling recently described by the Kraszewski group [11] for the synthesis of simple O-alkyl and aryl esters of nucleoside 3Ј,5Ј-cyclic phosphates offers a workable method for the introduction of structurally more complex enzymatically removable phosphate protecting groups, such as 3-acetyloxy-2,2-bis-(ethoxycarbonyl)propyl (in 1 and 4), 4-acetylthio-2,2-dimethyl-3-oxobutyl (in 2), and 4-(tert-butyldisulfanyl)-2,2dimethyl-3-oxobutyl (in 3) groups (Figure 1). In addition, data on the stability of the cyclic phosphotriesters (i.e., 1-4) and their conversion into cyclic diesters is given.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Accordingly, an alternative method is needed for the efficient protection of 3Ј,5Јcyclic phosphodiesters with enzymatically removable groups. We now show that the oxidative coupling recently described by the Kraszewski group [11] for the synthesis of simple O-alkyl and aryl esters of nucleoside 3Ј,5Ј-cyclic phosphates offers a workable method for the introduction of structurally more complex enzymatically removable phosphate protecting groups, such as 3-acetyloxy-2,2-bis-(ethoxycarbonyl)propyl (in 1 and 4), 4-acetylthio-2,2-dimethyl-3-oxobutyl (in 2), and 4-(tert-butyldisulfanyl)-2,2dimethyl-3-oxobutyl (in 3) groups (Figure 1). In addition, data on the stability of the cyclic phosphotriesters (i.e., 1-4) and their conversion into cyclic diesters is given.…”
Section: Introductionmentioning
confidence: 55%
“…[11] Accordingly, thymidine 3Ј-H-phosphonate (9) was prepared by the acid-catalysed detritylation of 5Ј-O-(4,4Ј-dimethoxytrityl)thymidine-3Ј-Hphosphonate (8). [11] Accordingly, thymidine 3Ј-H-phosphonate (9) was prepared by the acid-catalysed detritylation of 5Ј-O-(4,4Ј-dimethoxytrityl)thymidine-3Ј-Hphosphonate (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Work by Kraszewski and Stawinski demonstrated that a range of functionalized hydrogen phosphonates were generated through the reaction of nucleosides with diphenylphosphite . This process was highly substrate dependent, and while some substrates worked quite well, others afforded mixtures . Following a number of screening attempts, we were delighted to discover that this chemistry was successful for the synthesis of our required intermediate, and moderate yields could be generated by simply stirring a pyridine solution of diphenylphosphite with pentaerythritol.…”
Section: Resultsmentioning
confidence: 99%
“…The yield (10 %) was, however, lower than that obtained using diphenyl phosphite as the phosphitylating agent. Attempts to prepare phosphoramidate 1 by oxidative coupling,12,14 i.e., by iodination of the 5′‐[4‐(acetylthio)‐2,2‐dimethyl‐3‐oxobutyl H ‐phosphonate] and subsequent displacement of iodine from the iodophophate with L ‐alanine methyl ester, failed.…”
Section: Resultsmentioning
confidence: 99%